The Relationship between Lower Extremity Stiffness with Selected Biomechanical Variables during Vertical Jumps in Healthy Active Men - Mohamad Amin Mohamadian; Heidar Sadeghi; Mehdi Khaleghi Tazji (Biyumikānīk-i varzishī)
Objective: Stiffness is a characteristic of viscoelastic structures and is an effective factor in sports movement biomechanics, which is an important factor in motion production and neuromechanical control of human body. The purpose of this study is to determine the relationship between lower extremity stiffness and selected biomechanical variables during vertical jumps. Methods: 20 male physical education students participated voluntarily in this study. They performed Vertical hopping tests in three styles, bilateral, unilateral on dominant leg and unilateral on non-dominant leg, with three strategies, preferred, controlled (frequency 2.2 Hz) and maximal to determine the stiffness of the lower extremity. They also performed Squat jump and Countermovement jump tests to determine the mechanical power, take-off velocity and the efficiency of the stretch-shortening cycle. Results: Among the stiffness variables with different strategies, only the preferential lower extremity stiffness showed a significant and negative correlation with the velocity of the center of mass (p< 0.05). Conclusion: Bases on the research findings, it can be argued that lower extremity stiffness is not mush effective in vertical jumps. It is not effective in stretch-shortening cycle either but there may probably be some optimal value for it.